War Trophies, War Memorabilia, and the Iconography of Victory in the British Empire. (October 2019) - Wellington, Jennifer
Cultural efforts to mobilise populations behind the war in Britain and its Dominions, Canada and Australia – especially through the exhibition of war trophies – solidified after the Armistice into state-supported institutions creating and promoting a culture of victory. This culture was most pronounced, and most centralised, in Australia. Wartime propaganda institutions grew into national war museums which effectively froze the victorious national war effort, and the moment of triumph, in three-dimensional form. The institutions, and the people who ran them, did not demobilise with the peace. These museums used substantially the same objects and techniques they had used in wartime to support the war effort to create a postwar narrative in which victory established a clear (and martial) national identity, and also justified the war itself. At the same time, the narrative of a British imperial victory was used to create claims of unity which denied the reality of divisions in society. Trophies wrested from wartime enemies were used as pride-inducing objects to fundraise for peace, and fashioned into war memorials that were at once sites of mourning and monuments celebrating military dominance. Visions of postwar peace and progress could not be disentangled from victory and the violence that enabled it.